Cultural Scripts of Traumatic Stress: Outline, Illustrations, and Research Opportunities - Chentsova-Dutton, Yulia; Maercker, Andreas (Frontiers in Psychology, 2019)
As clinical-psychological scientists and practitioners increasingly work with diverse populations of traumatized people, it becomes increasingly important to attend to cultural models that influence the ways in which people understand and describe their responses to trauma. This paper focuses on potential uses of the concept of cultural script in this domain. Originally described by cognitive psychologists in the 1980s, scripts refer to specific behavioral and experiential sequences of elements such as thoughts, memories, attention patterns, bodily sensations, sleep abnormalities, emotions and affective expressions, motivation, coping attempts, and ritualized behaviors that are relevant to posttraumatic adjustment. We differentiate between experiences of traumatic stress that are scripted (e.g., cultural explanations are available) versus unscripted. Further characteristics such as script tracks, the effect of script interruptions, and contextual fit of scripts with other cultural models are also described. We consider examples of traumatic stress associated with war and organized, sexualized violence from “Western” and “non-Western” world regions. The concluding part of this review describes a number of possibilities for methodological approaches to assessment of cultural scripts. Capturing central elements of the script(s) of trauma would aid psychological researchers and clinicians in understanding the experiences of trauma in cultural context, which could ultimately lead to better clinical service opportunities worldwide.